MEMBANGUN INKLUSIVITAS KEBERAGAMAAN ANTARA MASYARAKAT DENGAN PENYANDANG TUNA DAKSA MELALUI BIMBINGAN FIKIH IBADAH DI “RUMAH KASIH SAYANG” DESA KREBET JAMBON PONOROGO - Afif Syaiful Mahmudin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
Persons with physical disabilities recorded under the auspices of the "Rumah Kasih Sayang" institution are 12 people. Ideally, the practice of worship should be carried out easily by everyone, but in fact there are still many people with disabilities who experience difficulties in implementing it, not even a few of them have left worship because of low religious-related understanding and lack of motivation from the community to include persons with disabilities. carry out daily worship obligations. These problems are experienced by people with disabilities, especially physically disabled in the "Rumah Kasih Sayang" in Krebet village. People with disabilities by the community are considered as groups who are no longer obliged to worship, they are sufficiently fostered with a variety of skills obtained from the institution, empowered by breeding goats from compensation without even being physically invited to pray together in the mosque or prayer room. Religious inclusiveness needs to be built between the community and the physically disabled, the community must be given an understanding that as long as the disabled person meets the taklif provisions, there is no privilege that disqualifies the obligation of worship for the disabled. The research questions are: 1) What are the implications of the fiqh guidance of worship for the disabled in the "Rumah Kasih Sayang" Krebet Jambon Village? 2) What are the implications of fiqh material for worship for the people of Krebet Jambon Village ?. To answer the formulation of the problem, the researcher used a Participatory Action Research (PAR) approach. The results of this study are: 1) Deaf people can practice well the procedures of daily worship in accordance with the fiqh hospitality of disabled people while being able to carry out the obligation to worship together with the surrounding community. 2) People get new insights about fiqh worship for people with disabilities, changing their negative stigma towards disabled people and leading to the realization of an inclusive religious culture in Krebet Jambon Ponorogo Village.